Human Resource Performance Improvement Based Upon Job Autonomy, Intrinsic Motivation and Job Demands - Fatkhuri Fatkhuri; Ali Jufri; Tri Budi Prasetyo (IAIN Syekh Nurjati Cirebon, 2020)
ABSTRACT Many factors can improve the performance of HR in the organization. One of them is to give freedom to perform job duties and responsibilities of an employee (job autonomy). Study of the need for the autonomy of work influence on job performance is still very rare, so it becomes very interesting to be studied. This study aimed to examine how to improve HR performance-based model of job autonomy and intrinsic motivation and willingness to meet the demands of work. The population in this study is the human resources at the Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana Kabupaten Tegal as many as 97 respondents. Data obtained from questionnaires and analyzed with data analysis tools PLS. The results of data analysis showed that the job autonomy has positive and significant effect on the job performance, job autonomy has not significant effect on job demands. Intrinsic motivation has positive and significant effect on the job performance, intrinsic motivation significantly influence the job demands, and the job demands has not significant effect on job performance. The future research should include other variables as an intervening variable to provide solutions in improving human resource capacity to meet the job. Key words : job autonomy, job demand, intrinsic motivation, job performance.